2014
DOI: 10.1111/head.12439
|View full text |Cite
|
Sign up to set email alerts
|

KCNK18 (TRESK) Genetic Variants in Italian Patients With Migraine

Abstract: Our study shows the presence of several KCNK18 gene mutations in both migraine with aura and migraine without aura. However, the precise role of this gene in migraine predisposition deserves further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…In the present study, we found that polymorphism c.28A>G, as well as mutation c.328T>C of KCNK18 gene, occurred with similar frequency in the control group and migraine patients. It corresponds with previous studies of c.28A>G [ 13 , 20 ] and c.328T>C [ 13 , 37 ] variants. Whereas, Rainero et al [ 20 ] found the mutation only in migraine patients, both MA and MO.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we found that polymorphism c.28A>G, as well as mutation c.328T>C of KCNK18 gene, occurred with similar frequency in the control group and migraine patients. It corresponds with previous studies of c.28A>G [ 13 , 20 ] and c.328T>C [ 13 , 37 ] variants. Whereas, Rainero et al [ 20 ] found the mutation only in migraine patients, both MA and MO.…”
Section: Discussionsupporting
confidence: 92%
“…It corresponds with previous studies of c.28A>G [ 13 , 20 ] and c.328T>C [ 13 , 37 ] variants. Whereas, Rainero et al [ 20 ] found the mutation only in migraine patients, both MA and MO. It was also previously found in Polish patients with MA [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This mutation has already been well characterized and shown to be migraine-related but not to influence the activity of the TRESK K2P potassium channel encoded by KSNK18 [ 24 ]. Other studies on this variant also showed relationship to migraine with typical aura [ 25 ]. Accordingly, we found the KCNK18 mutation in a patient with migraine without aura.…”
Section: Discussionmentioning
confidence: 83%
“…Surprisingly, other mutations that inactivate TRESK were not correlated with migraine [57,58]. A number of KCNK18 missense variants (R10G, A34V, C110R, S231P, A233V) were also identified in unrelated sporadic migraine and control cohorts [20], as well as in Italian migraine patients [59]. Some variants (R10G, S231P, and A233V) did not appear to significantly affect TRESK current, [57] but, unexpectedly, the C110R variant, despite producing a complete loss of TRESK function, did not show an association with the disease, as it was expressed both in control and sporadic migraine cohorts.…”
Section: Tresk and Migrainementioning
confidence: 99%